(untitled) - Zhang, Haifei; Li, Kai (Indian Journal of Pharmaceutical Education and Research)
Background: Osteoporosis is a common skeletal condition marked by decreased bone density and impaired bone microarchitecture, which substantially increases the fracture risks. This systemic condition results from a disproportion in bone homeostasis, when bone resorption exceeds bone formation. Objectives: This work focuses to study the anti-osteoporotic efficacy of bilobetin against Overiectomy (OVX)-induced osteoporosis in rat model. Materials and Methods: The OVX surgery was done on the experimental rats to develop osteoporosis, followed by a 12-week treatment with bilobetin. The biomechanical parameters were evaluated in the femur bones of experimental rats. The concentrations of bone turnover biomarkers were evaluated using kits. Furthermore, the levels of Calcium (Ca) homeostasis markers, oxidative stress indicators, inflammatory biomarkers, and bone remodeling marker proteins were evaluated using kits. Results: The results of this work indicated that bilobetin treatment effectively regulated the biomechanical parameters of femur bones, bone turnover markers, and calcium homeostasis in the OVX-induced rats. Furthermore, bilobetin treatment also decreased the inflammatory biomarkers, reduced oxidative stress responses via elevating antioxidants, increased Runx2 and OPG concentrations, and reduced RANKL levels in OVX rats. Conclusion: The present findings elucidated the anti-osteoporosis effects of bilobetin against OVX-induced rats. The present data indicated the advantageous effects of bilobetin in mitigating the osteoporosis condition in OVX rats, thereby establishing it as a promising pharmacological treatment for osteoporosis management.
Keywords: Bone Remodeling; Calcium Homeostasis; Bilobetin; Overiectomy; RANKL/OPG Pathway.